The Model of Listening CEFR-Based Test Specification for Higher Education - Ifan Iskandar; Ali Satri Efendi; Imam Santosa (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
The Common European Framework of Reference (CEFR) for Languages offers a prevalent underpinning for the development of languages syllabuses, curriculum guidelines, assessments, and textbooks. This research aimed to design appropriate CEFR-based for languages English listening test specifications for S1 English Study Program. Descriptive qualitative interpretative was used as research design of this research. The data of this research consisted of the curriculum of English language education program which focused on listening courses of 5 universities in Jakarta. The data showed English language competence or ability for undergraduate graduates of English language study programs and abilities based on CEFR. The result showed that the five universities have the level of CEFR in A1 (9,7%), A2 (11%), B1 (7,3%), B2 (8,6%), C1 (5,9%), and C2 (0%) of CEFR levels. The result is a basis for the writer to design English listening test specifications that range from A1 to C1 alienated into Basic Listening, Intermediate Listening, and Advanced Listening. Based on that, the proposed test specifications were created. The writer adapts IELTS as the standardized test to determine the number of sections, question types, number of items, and time allocation.